The Influence of Brand Image, and Sharia Label on Savings Decisions of Customers at PT Bank Syariah Indonesia Tbk KCP Jember Gajah Mada - Ludita Cosa Arlian; Siti Masrohatin; Nurul Setianingrum; Hersa Farida Qoriani; Moch. Chotib (Riviera Publishing, 2024)
This study aims to analyze the effect of brand image and sharia label on saving decisions on customers of PT Bank Syariah Indonesia Tbk KCP Jember Gajah Mada. Bank Syariah Indonesia is one of the largest Islamic financial institutions in Indonesia that provides banking products and services according to sharia principles. Factors such as brand image and the existe nce of sharia labels are considered to have an important role in influencing customer decisions to save at Islamic banks. The research method used is quantitative with data collection techniques through questionnaires distributed to Bank Syariah Indonesia customers at KCP Jember Gajah Mada. The data obtained were analyzed using multiple linear regression to determine the effect of each independent variable on saving decisions. The results showed that brand image, and sharia label simultaneously and partially had a significant effect on customer saving decisions. Brand image has a positive and significant effect, which shows that the positive image of Islamic banks can increase customer interest in saving. In addition, the sharia label, which shows compliance with sharia principles, also makes a significant contribution in influencing customer decisions. In conclusion, brand image, and sharia label are important factors that influence customer decisions in saving at Bank Syariah Indonesia. Therefore, the bank is expected to continue to strengthen the brand image, provide education about sharia products, and maintain the integrity of the sharia label to increase customer loyalty and trust.